EVALUATION OF DIURETIC ACTIVITY OF ALCOHOLIC EXTRACT OF FLOWER BUDS OF NEOLAMARCKIA CADAMBA IN ALBINO RATS - AKASH; SINGH, AMAR PAL; SINGH, AJEET PAL (International Journal of Current Pharmaceutical Research, 2026)
Objective: To study the diuretic activity of Alcoholic Extract of Flower buds of Neolamarckia cadamba by Lipschitz method in albino Wistar rats. Methods: Metabolic cages were utilised to test the diuretic effect of Alcoholic Extract of Flower Buds of Neolamarckia cadamba in four Albino Wistar rats. Group I, the normal control, got vehicle (10 ml/kg or 1 ml of 0.9% NaCl/100 gm), group II received Frusemide (10 mg/Kg, p. o), and groups III and IV received low (200 mg/kg) and high (400 mg/kg) dosages of Alcoholic Extract of Neolamarckia cadamba flower buds Following Neolamarckia cadamba Alcoholic Extract treatment, rats were hydrated with saline (15 ml/kg, p. o) and put in metabolic cages at 25 °C±0.5 °C. Animals went 5 h without food or water. Each metabolic cage's urine volume was assessed after 5 and 24 h. Total urine volume, ion concentration (Sodium, Potassium, Chloride), and pH were measured. Results: In this model when compared to control group the Alcoholic Extract of Flower buds of Neolamarckia cadamba treated groups at different dose levels (200 and 400 mg/kg) have noted with significant increase in the urine volume and also significantly enhanced the excretion of Sodium, Potassium and Chloride ions in urine. In the urine pH no difference has been found. Conclusion: Results showed that single dose administration of standard Furosemide and Alcoholic Extract of Flower buds of Neolamarckia cadamba significantly increased the urine output along with an increase in elimination of Sodium, Potassium, and Chloride ions. Alcoholic Extract of Flower buds of Neolamarckia cadamba, 400 mg/Kg produced a comparable diuretic activity with standard Frusemide.